The missing link in marine ecosystem-based management - Peter Arbo; Thuy Pham Thi Thanh (European Regional Science Association (ERSA), 2014)
The missing link in marine ecosystem-based management Peter Arbo, University of Tromsø ? The Arctic University of Norway Phạm Thị Thanh Thủy, University of Nha Trang The Arctic region is receiving growing attention. There is increasing interest in exploiting the natural resources and the new sea routes that open as the sea ice is retreating and new technology and infrastructure make the Arctic Ocean more accessible. However, the environmental impacts of a melting Arctic and the consequences of increasing human activity also arouse serious concern. From many quarters, the need for a sustainable ecosystem-based management of the Arctic Ocean is therefore stressed. This paper takes a closer look at the shortcomings of the ecosystem approach. Environmental governance of the Arctic Ocean is not only facing the challenges of creating a common framework across highly different coastal states. The ecosystem approach itself has limitations that need to be addressed. Our contention is that so far the main focus has been on the natural ecosystems while the regulation of industrial activities, which is a prerequisite for balancing ocean uses with the maintenance of ecosystem integrity, has largely been ignored. The paper thus starts with a discussion of what we have called the missing link in ecosystem-based management. We point out that the attempts to establish this new governance framework primarily have been about identifying valuable and vulnerable habitats and species, assessing the cumulative impacts of human activity, and setting up monitoring systems for measuring the health of the ecosystems. The more complicated issues of how to regulate and coordinate expanding industrial activities have received more scant attention. After this, we analyze some of the challenges associated with including the patterns of human activity, regulating industries, and dealing with user conflicts. This is done by a comparative study of the relationship between the offshore oil and gas industry and the seafood industry in Norway and Vietnam. In the case study, we highlight, among other things, the importance of power asymmetries, transparency, differences in the level of development, and mechanisms for institutional coordination. The paper concludes with a discussion of lessons to be learned for integrated marine governance.
Keywords: Z13; Z18; 330; Ecosystem-based management; the Arctic Ocean; regulation of industrial acitivity; oil versus fisheries